2019
DOI: 10.1016/j.crma.2018.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Approximation locale précisée dans des problèmes multi-échelles avec défauts localisés

Abstract: Présenté par £££££ RésuméNous poursuivons l'étude initiée dans [3] de problèmes multi-échelles avec défauts, dans le cadre de la théorie de l'homogénéisation, spécifiquement ici pour une équation de diffusion avec un coefficient de la forme fonction périodique perturbée par une fonction L r (R d ), 1 < r < +∞, modélisant un défaut local. Nous esquissons la démonstration du fait que le correcteur, dont l'existence a été prouvée dans [3,4], permet d'approcher la fonction solution de l'équation originale avec la … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…We point out that, to our knowledge, the result in Theorem 1.3 is new and extends the results obtained in [3,4,5,6,14] to more general elliptic equations in at least two perspectives:…”
Section: Introduction and The Main Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…We point out that, to our knowledge, the result in Theorem 1.3 is new and extends the results obtained in [3,4,5,6,14] to more general elliptic equations in at least two perspectives:…”
Section: Introduction and The Main Resultssupporting
confidence: 71%
“…We also point out an important fact. With less regularity than in [5,6], however we obtain sharper L 2 convergence rates than in [5,6]. Indeed in [5,6] it is shown that if the matrix A has the form…”
Section: Introduction and The Main Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…In the periodic setting, such results are provided by Avellaneda and Lin's theory [7]. But, as shown in [9] (see also [6,10]), the periodicity assumption is not necessary to these local estimates: they can be obtained in various frameworks, as long as the correctors and the potential (defined by (14) and ( 22)) associated with the matrix A are strictly sublinear and as long as the homogenized matrix is constant.…”
Section: Introductionmentioning
confidence: 99%